2015
DOI: 10.1002/tox.22215
|View full text |Cite
|
Sign up to set email alerts
|

Global metabolic profiling for the study of Rhizoma Paridis saponins‐induced hepatotoxicity in rats

Abstract: Rhizoma Paridis saponins (RPS) is a traditional Chinese medicine (TCM) from the plant Paris polyphylla var. yunnanensis (Fr.) Hand.-Mazz. Despite its potentially clinical utility such as anticancer and anti-inflammation, it has slight side effects and toxicity as previous report. In this work, 90-day administration of RPS induced liver injury. H-NMR- and GC/MS-based metabonomic analyses in conjunction with histopathological examinations, blood biochemistry and hepatic phase I and II enzymes assays were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Lists of herbs and concoctions that were hepatotoxic or hepatoprotective, their respective causality levels, and number of cases are compiled in Tables 1 to 5. 9,13-46…”
Section: Resultsmentioning
confidence: 99%
“…Lists of herbs and concoctions that were hepatotoxic or hepatoprotective, their respective causality levels, and number of cases are compiled in Tables 1 to 5. 9,13-46…”
Section: Resultsmentioning
confidence: 99%
“…The saponins in Paris saponins have many pharmacological properties, such as anti-tumor [40,41], hemostatic [42], anti-bacterial [43], anti-inflammatory [44], angiogenesis-inhibitory [45] and immune-regulatory [46] effects. However, in recent years, some studies have reported the in vivo hepatotoxicity of Paris saponins [3,4,5,6,7]. The purpose of the present study was to investigate the hepatotoxicity of the four main saponins from Rhizoma paridis in vitro and to unravel the cellular and molecular mechanisms involved.…”
Section: Discussionmentioning
confidence: 97%
“…Rhizoma paridis, a liliaceous plant of the Yunnan Paris or the dried rhizome of the seven-leaf flower, is a frequently used traditional Chinese medicine in clinics due to its numerous pharmacological effects [1,2]. Recently, some studies reported that an excess dose of Rhizoma paridis produced liver injury due to its saponin components [3,4,5,6,7]. However, the hepatotoxicity of various saponins in Rhizoma paridis and their mechanism of action have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…For thousands of years, Paridis saponin (PS) and its components have always been used as hemostatic regulatory, antifungal, anti-inflammatory, antimicrobial, and antibacterial medications in China ( White et al, 2015 ; Moldogazieva et al, 2018 ). Recent studies have reported promising roles of PS in the regulation of glycolytic and lipid metabolism ( Man et al, 2017 ; Man et al, 2020 ). In addition, the PSII extract has been approved as an antitumor agent for many years in China, but its mechanism of action is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…yunnanensis used as an anticancer drug in traditional Chinese medicine (TCM) which is also an active component of Paris saponin II (PSII), has shown a strong antitumor power in various cancers, such as hepatocellular carcinoma (HCC) ( Cheng et al, 2008 ), lung cancer ( Man et al, 2015 ), and ovarian cancer ( Xiao et al, 2009 ). Recent studies have reported promising roles of PS in the regulation of glycolytic and lipid metabolism ( Man et al, 2017 ; Man et al, 2020 ). All these results indicate that PSII may be a valuable anti-HNSCC agent.…”
Section: Introductionmentioning
confidence: 99%